Nurse on the front line to COVID-19: The experience of the lived reality (Research, Society and Development, 2020)
During the care process, especially when working during a pandemic, the nurse may be subjected to a level of stress that will cause physical and psychological damage. In this sense, the present study aims to identify and analyze the stressors experienced by health professionals on the front lines of the fight against COVID-19. This is a descriptive study that seeks to describe certain phenomena or actions. With the option of a qualitative approach, the research found in the experience report, an opportunity to learn about integrative and complementary practices for social well-being. From the report, it was possible to reflect on relevant elements to be considered. For discourse analysis, we present the following categories: Feelings experienced in the face of the pandemic from the perspective of the health professional; Concern about maintaining mental health and the impact of working conditions and loss of colleagues. It is concluded that it is necessary that intervention actions are carried out aiming at the commitment of the management, guaranteeing the safety of the working professional with the supply of personal protective equipment and also assistance aimed at the individual's mental health.